Healthcare and big data management - Shen, Bairong (Springer, 2017)
The book addresses the interplay of healthcare and big data management. Thanks to major advances in big data technologies and precision medicine, healthcare is now becoming the new frontier for both scientific research and economic development. This volume covers a range of aspects, including: big data management for healthcare; physiological and gut microbiota - data collection and analysis; big data standardization and ontology; and personal data privacy and systems level modeling in the healthcare context. The book offers a valuable resource for biomedical informaticians, clinicians, health practitioners and researchers alike.
Keywords: Medical informatics.; Big data -- Management.; Medicine -- Data processing.; elektronické knihy; electronic books